2010
DOI: 10.4300/jgme-d-09-00103.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Online Assessment of Orthopedic Surgery Residents' Cognitive Skills and Preparedness for Carpal Tunnel Release Surgery

Abstract: The online perception of preparedness measure and the cognitive skills assessment both are valid and reliable predictors of readiness to successfully pass a cadaveric motor skills test of carpal tunnel release surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Shanedling et al found that two online instruments designed to assess residents' perception of preparedness and cognitive skills were both valid and reliable predictors of their readiness to successfully pass a cadaveric motor skills test of carpal tunnel release 86 .…”
Section: Cadaver and Computer Software Toolsmentioning
confidence: 99%
“…Shanedling et al found that two online instruments designed to assess residents' perception of preparedness and cognitive skills were both valid and reliable predictors of their readiness to successfully pass a cadaveric motor skills test of carpal tunnel release 86 .…”
Section: Cadaver and Computer Software Toolsmentioning
confidence: 99%
“…In many ways, these advances have resulted in improved measurement because innovative formats allow test items to better represent the constructs they are written to measure. For example, in testing of health science students and medical professionals, skill in performing complicated surgical procedures can be tested using video or even three-dimensional simulations of specific anatomical regions (Shanedling, Van Heest, Rodriguez, Putnam, & Agel, 2010). In the testing of mathematics or statistics, test items may integrate spreadsheets or plots to better gauge students' understanding.…”
Section: Item-writing Guidelinesmentioning
confidence: 99%